2017
DOI: 10.1002/ece3.2710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil C:N:P stoichiometry on biomass allocation in the alpine and arid steppe systems

Abstract: Soil nutrients strongly influence biomass allocation. However, few studies have examined patterns induced by soil C:N:P stoichiometry in alpine and arid ecosystems. Samples were collected from 44 sites with similar elevation along the 220‐km transect at spatial intervals of 5 km along the northern Tibetan Plateau. Aboveground biomass (AGB) levels were measured by cutting a sward in each plot. Belowground biomass (BGB) levels were collected from soil pits in a block of 1 m × 1 m in actual root depth. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…Also, our results showed that soil C:P ratio values ranged from 4.46 to 20.48, when the mean value was 11.65, implying a phosphorous net mineralization. In which Paul [49] recorded that C:P ratio <200 referred to a net mineralization, while C:P ratio >300 referred to a net immobilization, and a C:P ratio ranging from 200 to 300 implied little change in the concentrations of soil soluble P. Our results revealed that the N:P ratio ranged between 0.77 and 1.68, with a mean value of 1.19, which indicated high microbial activity, whereas due to Wang et al [70] the N:P ratio was negatively correlated with microorganisms' activity and biomass in which N:P > 2 indicated biomass decline.…”
Section: Variability Of Soil Propertiesmentioning
confidence: 44%
“…Also, our results showed that soil C:P ratio values ranged from 4.46 to 20.48, when the mean value was 11.65, implying a phosphorous net mineralization. In which Paul [49] recorded that C:P ratio <200 referred to a net mineralization, while C:P ratio >300 referred to a net immobilization, and a C:P ratio ranging from 200 to 300 implied little change in the concentrations of soil soluble P. Our results revealed that the N:P ratio ranged between 0.77 and 1.68, with a mean value of 1.19, which indicated high microbial activity, whereas due to Wang et al [70] the N:P ratio was negatively correlated with microorganisms' activity and biomass in which N:P > 2 indicated biomass decline.…”
Section: Variability Of Soil Propertiesmentioning
confidence: 44%
“…In the three microhabitats, there were no significant differences in the ratios of C:N and C:P. These two ratios reached their highest values under dead shrubs and lowest values in exposed ground. The ratios of C:N and C:P signified the ability of plants to assimilate C when simultaneously absorbing N and P (Rong et al, 2015), and the increased C:N and C:P ratios indicated an increase in the efficiency with which N and P are used (He et al, 2006;Wang et al, 2017). The higher efficiency value for moss is consistent with greater allocation to cell wall relative to cell contents under dead shrubs rather than in exposed ground (Waite and Sack, 2011).…”
Section: Plant Stoichiometry Of S Caninervismentioning
confidence: 86%
“…al. [ 118 ] an N:P ratio > 2 shows a decline in biomass. Our results revealed a low value of 0.06 for all land use indicates an increase in biomass production.…”
Section: Discussionmentioning
confidence: 99%